Depolarization affects the lateral microdomain structure of yeast plasma membrane. (8th December 2014) - Herman, Petr; Vecer, Jaroslav; Opekarova, Miroslava; Vesela, Petra; Jancikova, Iva; Zahumensky, Jakub; Malinsky, Jan
<x xml:space="preserve">Abstract</x> We report the transmembrane voltage‐induced lateral reorganization of highly‐ordered lipid microdomains in the plasma membrane of living Saccharomyces cerevisiae. Using trans‐parinaric acid (all‐trans‐9, 11, 13, 15‐octadecatetraenoic acid) as a probe of lipid order and different methods of membrane depolarization, we found that depolarization always invokes a significant reduction in the amount of gel‐like microdomains in the membrane. Different depolarization mechanisms, including the application of ionophores, cell depolarization by an external electric field, depolarization by proton/hexose co‐transport facilitated by HUP1 protein and a reduction of membrane potential caused by compromised respiration efficiency, yielded the same results independently of the yeast strain used. The data suggest that the voltage‐induced reorganization of lateral membrane structure could play significant role in fast cellular response to acute stress conditions, as well as in other membrane microdomain‐related regulatory mechanisms.